Iodine Deficiency as a Social Problem Endemic Goiter as a Disease of the Whole Organism - Ikromjonovna, Kariyeva Halima (European Journal of Life Safety and Stability (2660-9630), 2021)
The article considers iodine deficiency as a social problem. Endemic goiter has been studied as a disease of the whole organism. The causes and consequences of iodine deficiency have been studied. Recommendations for the diagnosis and treatment of this disease are given.